REGULASI PEMANFAATAN AIR BAWAH TANAH DI KOTA DENPASAR - PRADNYANINGRUM, PUTU SISKHA; SARI, PUTRI AYU DEVY PERMATA; HARTAWAN, I PUTU (Ganec Swara, 2025)
Global climate change has had a significant impact on human life on earth. Many phenomena and problems occur as a result of massive climate change. One of them is the beginning of a clean water crisis in all corners of the world, including in big cities in Indonesia. The occurrence of the clean water crisis is said to be caused by rapid evaporation and causing a decrease in the volume of groundwater. The decline in groundwater levels not only results in a decrease in the availability of clean water, but can also have other major impacts such as seawater intrusion and land subsidence. In this regard, with the aim of ensuring the sustainability of the availability of water and water sources and ensuring the preservation of water functions and water sources to support the sustainability of development, the government has made efforts to control the use of groundwater as outlined in several laws and regulations, ministerial decrees, and into regional regulations. This study was conducted to formulate a summary of the regulation of groundwater utilization in Denpasar City. The method approach carried out is to use normative legal research. The result is that since 2022, the management of groundwater utilization permits in Denpasar City has become the authority of the central government considering that Bali Province is included in the national strategic river area. Where, in the previous year, the people of Denpasar City applied for a permit for the use of groundwater to the Denpasar City Government and the Bali Provincial Government. In addition, currently the government also has a policy in regulating the use of groundwater for non-business actors with certain provisions